Transformasi Media Digital dan Moderasi Beragama: Fenomena Politisasi Agama di Indonesia - Achmad Zaky Nauval; Tri Ahmad Tommy Sinambela; Khairiyah Ramadhani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Indonesia is a multicultural country, so if you look at it, an approach in religion that emphasizes tolerance, mutual respect and open dialogue between various religions and beliefs is needed. In the political context, freedom of religion and belief can serve as a tool to prevent the politicization of religion. The politicization of religion seems to be the target of political contestation in Indonesia with digital media being its weapon that forms a polarization. The method used in this study is a qualitative descriptive method. The selection of this method is based on the purpose of the research, which is to understand the reality of the implementation of elections, the strengthening of religious politicization in Indonesia. The results of scientific work show that the Government of Indonesia can elaborate with digital media in developing freedom of religion and belief as an effort to prevent the politicization of religion that has been polarized.